The Effect of Midwifery Preparation Program for Nurse and Midwifery License Examination among Air Force Student Nurses - Wannarit, La-Ongdao (Journal of The Royal Thai Army Nurses, 2023)
This quasi-experimental research aimed to study the effect of a midwifery preparation program for nurses and midwifery license examination among Air Force Student Nurses. The sample group was fifty-six Air Force Nurses who completed the degree in 2022, selected by purposive sampling. The research instruments comprised a midwifery preparation program, with a validity index (CVI) equal to 1.00, and two sets of midwifery knowledge tests, with a CVI equal to 0.88 and 0.90, respectively. Reliability was analyzed using Kuder and Richardson (KR-20) 0.72 and 0.76, respectively. The test-retest method was used to analyze the equivalence of parallel examinations, yielding the Pearson correlation coefficient of 0.91. The research data were analyzed using Paired T-test statistics. The research results found that after participating in the program, the sample group had a higher mean score than before participating in the program, statistically significant (t=15.352, p<.001). 100% of samplings passed the nurses and midwifery licensure examination. The results of this study can be used as a guideline for nursing instructors to prepare for the midwifery course to take the examination and receive a license to be a registered nurse and midwifery.